2012
DOI: 10.1111/j.1747-1346.2011.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cross‐Pressures of Religion and Contact with Gays and Lesbians, and Their Impact on Same‐Sex Marriage Opinion

Abstract: This article examines the influence of two cross-pressures, religion and contact with gay individuals in the United States, on same-sex marriage opinion. Close relationships with gays and lesbians may influence people of varying faiths differently or not at all. Results indicate that despite religious teachings against homosexuality, people of most religious traditions are more likely to support same-sex marriage when they have a close relationship with a gay individual. The effects are the greatest for black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
0
31
0
1
Order By: Relevance
“…In particular, Wald, Owen, and Hill () argued that these views result from “messages from the pulpit,” where churchgoers receive political cues on social issues (see also Crawford and Olson ; Fetzer ). Most recently, Bramlett () examined the cross‐pressure created by religious values and contact on attitudes about a constitutional amendment banning same‐sex marriage, finding that contact (along with the closeness of the contact) had the largest effects on black evangelicals and Latino Catholics. Lewis () likewise demonstrated that the contact effect is smaller among conservative‐leaning groups, such as evangelicals and self‐identified conservatives, but found that contact still has a significant effect even among these subgroups.…”
Section: The Intergroup Contact Effect and Ambivalence About Gays Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Wald, Owen, and Hill () argued that these views result from “messages from the pulpit,” where churchgoers receive political cues on social issues (see also Crawford and Olson ; Fetzer ). Most recently, Bramlett () examined the cross‐pressure created by religious values and contact on attitudes about a constitutional amendment banning same‐sex marriage, finding that contact (along with the closeness of the contact) had the largest effects on black evangelicals and Latino Catholics. Lewis () likewise demonstrated that the contact effect is smaller among conservative‐leaning groups, such as evangelicals and self‐identified conservatives, but found that contact still has a significant effect even among these subgroups.…”
Section: The Intergroup Contact Effect and Ambivalence About Gays Andmentioning
confidence: 99%
“…Most of the scholarly literature has examined the effect that contact with gays/lesbians has on increasing support for gay rights. What effect, if any, contact has on creating cross‐pressure or ambivalence among citizens’ attitudes on gay rights, however, has received far less scholarly attention (although for an exception, see Bramlett ). Following research by Alvarez and and Brehm (1995, 1997, 2002), I use heteroskedastic regression to demonstrate that interpersonal contact with gays and lesbians induces ambivalence or cross‐pressure among citizens with conservative‐leaning predispositions (conservatives, Republicans, and evangelical Christians) while having the opposite effect among those with liberal‐leaning predispositions (liberals, Democrats, and nonevangelicals).…”
mentioning
confidence: 99%
“…Several authors have found significant effects for religious affiliation with the greatest opposition to same-sex marriage coming from Protestants, especially evangelical Protestants, and those identifying themselves as born again (Bramlett 2012;Bushong 2011;Campbell and Monson 2008;Denton Jr. 2005;Drenner 2011;Ellison et al 2011;Guth et al 2006;Hines 2011;McKenzie and Rouse 2013;Miller 2009;Olson et al 2006;Sherkat et al 2010;Sherkat et al 2011). The religious variable with the greatest impact across most of these studies was religious commitment or religiosity.…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 98%
“…Religion has also proved to have significant effects, with the greatest opposition to same‐sex marriage coming from Protestants, especially evangelical Protestants, and those identifying themselves as born again (Bramlett, ; Bushong, ; Daniels, ; Drenner, ; Ellison, Acevedo, and Ramos‐Wada, ; Hines, ; McKenzie and Rouse, ; Sherkat, de Vries, and Creek, ; Sherkat et al., ; Armenia and Troia, ; Yen and Zampelli, ). The religious variable with the greatest impact across most of these studies was religious commitment or religiosity.…”
Section: Factors Influencing Opinion On Same‐sex Marriagementioning
confidence: 99%